Consumer Behaviour and Brand Preference of Britannia Biscuits - An empirical study with reference to Salem, Tamil Nadu - Maruthamuthu, K.; Krishnakumar, K.; Vasan, M. (Indian Journal of Marketing, 2006)
The biscuit market in India is estimated to be 1.1million tons p.a., valued at Rs.35billion. The unorganized sector accounts for over 50% of the market. The market has been growing at a CAGR of 6-7% p.a. Per capita consumption of biscuits in India is estimated at a low 1.5kgs, reflecting the huge potential for growth. Manufacturing was reserved for small-scale upto 1997, which put large players at a disadvantage. In the organized sector, Britannia and Parle are the only national players with dominant market shares. Other organized players include domestic players like ITC, Bakeman's, Champion, Kwality, Priya and MNC's like SmithKline Consumer, Kellogg's, Sara Lee, Heinz, Excelsia (Nestle) and United Biscuits.